2017
DOI: 10.1002/acm2.12142
|View full text |Cite
|
Sign up to set email alerts
|

Robust optimization of VMAT for lung cancer: Dosimetric implications of motion compensation techniques

Abstract: In inverse planning of lung radiotherapy, techniques are required to ensure dose coverage of target disease in the presence of tumor motion as a result of respiration. A range of published techniques for mitigating motion effects were compared for dose stability across 5 breath cycles of ±2 cm. Techniques included planning target volume (PTV) expansions, internal target volumes with (OITV) and without tissue override (ITV), average dataset scans (ADS), and mini‐max robust optimization. Volumetric arc therapy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…A scenario is commonly called 'error scenario', although in this work terminology 'treatment scenario' is used, see next section. Since becoming available in commercial treatment planning systems, robust optimisation has demonstrated the ability to improve target coverage robustness and/or organ at risk (OAR) sparing compared to PTV-based planning, in both proton [15][16][17][18][19][20][21] and photon therapy [22][23][24][25]. It must be noted however, that robust target coverage is generally one of many variables in the optimisation objective function and therefore is in competition with other objectives, such as OAR dose.…”
Section: Introductionmentioning
confidence: 99%
“…A scenario is commonly called 'error scenario', although in this work terminology 'treatment scenario' is used, see next section. Since becoming available in commercial treatment planning systems, robust optimisation has demonstrated the ability to improve target coverage robustness and/or organ at risk (OAR) sparing compared to PTV-based planning, in both proton [15][16][17][18][19][20][21] and photon therapy [22][23][24][25]. It must be noted however, that robust target coverage is generally one of many variables in the optimisation objective function and therefore is in competition with other objectives, such as OAR dose.…”
Section: Introductionmentioning
confidence: 99%
“…The robust optimization plan for intensity-modulated proton therapy (IMPT) is widely used for several treatment sites [9][10][11]. The photon robust optimization plan also facilitates significantly more robust dose distribution to targets and OARs than the PTV-based optimization plan [12][13][14][15][16][17][18]. This approach has been investigated to achieve coverage of the breast CTV with setup variations [12,13], or to cover the dose to moving targets through breathing cycles in lung tissue [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The photon robust optimization plan also facilitates significantly more robust dose distribution to targets and OARs than the PTV-based optimization plan [12][13][14][15][16][17][18]. This approach has been investigated to achieve coverage of the breast CTV with setup variations [12,13], or to cover the dose to moving targets through breathing cycles in lung tissue [14,15]. The robust optimization plan using partial-arc VMAT has been shown to be effective for targets at the periphery of the body because when the setup error occurs in the lateral direction, the depth of the tumor either increases or decreases [16].…”
Section: Introductionmentioning
confidence: 99%
“…The agreement between the planned nominal dose and dose evaluated on the 4DCT was better for the CMRO-plans than the PTV-plans[6]. Archibald-Heeren et al compared CMRO VMAT of lung cancer on a thorax phantom[24]. The authors found fewer maximum and minimum dose variations compared to other current treatment techniques such as internal target volume based planning as evaluated on a 4DCT[24].…”
mentioning
confidence: 99%
“…Archibald-Heeren et al compared CMRO VMAT of lung cancer on a thorax phantom[24]. The authors found fewer maximum and minimum dose variations compared to other current treatment techniques such as internal target volume based planning as evaluated on a 4DCT[24]. Zhang et al investigated the benefit of CMRO for five prostate cancer patients in which the CTV and OAR delineations were…”
mentioning
confidence: 99%